2021
DOI: 10.3390/jcm10245789
|View full text |Cite
|
Sign up to set email alerts
|

Anterior-Segment Swept-Source Ocular Coherence Tomography and Scheimpflug Imaging Agreement for Keratometry and Pupil Measurements in Healthy Eyes

Abstract: This study examines agreement between the devices Anterion® and Pentacam HR® used for corneal and pupil measurements in healthy eyes. The parameters compared between the two devices were: anterior Km (D), anterior K2 (D), anterior K1 (D), anterior K1 axis (°), anterior astigmatism (D), anterior K max (D), posterior Km (D), posterior K2 (D), posterior K1 (D), posterior K1 axis (°), posterior astigmatism (D), CCT (µm), thinnest point thickness (µm), thinnest point X-coordinate (mm), thinnest point Y-coordinate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(36 reference statements)
1
5
0
1
Order By: Relevance
“…Regarding the measurement of the corneal characteristics, the three instruments showed no signi cant difference in the measurement of astigmatism in the control group. Pérez Bartolomé et al [22] reached a similar conclusion after comparing Pentacam and Fourier-domain OCT (FD-OCT). This may be because the instruments show higher consistency among patients with regular astigmatism than in keratoconus patients [23].…”
Section: Diagnostic Validity Of the Keratoconus Screening Indicators ...mentioning
confidence: 70%
“…Regarding the measurement of the corneal characteristics, the three instruments showed no signi cant difference in the measurement of astigmatism in the control group. Pérez Bartolomé et al [22] reached a similar conclusion after comparing Pentacam and Fourier-domain OCT (FD-OCT). This may be because the instruments show higher consistency among patients with regular astigmatism than in keratoconus patients [23].…”
Section: Diagnostic Validity Of the Keratoconus Screening Indicators ...mentioning
confidence: 70%
“…SD of Anterion measurements was 1.34 mm and of Pentacam HR 1.60 mm. 15 In our study, Pentacam WO had the highest SD with 1.23 mm. A further group compared IOL Master 700 (Carl Zeiss Meditec AG) and OA-2000 (Tomey Corp.), both biometers based on swept-source OCT, in a dimly lit room.…”
Section: Discussionmentioning
confidence: 99%
“…The 95% LoA widths of every parameter were narrower than those in our study, and the authors concluded that these parameters cannot be used interchangeably. Perez-Bartolome et al [ 21 ] compared the anterior segment SS-OCT (Anterion, Heidelberg Engineering) and Pentacam HR for corneal and pupil measurements in healthy eyes. In their study, pupil diameter and angle kappa were significantly longer when using Anterion (5.74 ± 1.34 and 0.37 ± 0.18 mm, respectively) than when using Pentacam (3.82 ± 1.60 and 0.26 ± 0.14 mm, respectively).…”
Section: Discussionmentioning
confidence: 99%